Protótipo de sistema de rastreamento para veículos de transporte de cargas: uma abordagem com ferramentas e protocolos de código aberto - XAVIER, José Henrique Lemos (2022)
Vehicle tracking isn’t something new, whatever, with the outcome of news technologies in the world and the ascension of open-source software community turned these solutions, before a “black-box” only know by each manufacturer into something reachable to be used and operated by small and medium business operations. We utilize Thingsboard as foundation for the creating a tracking system completely independent of a specific hardware, allowing the user to choose the one which will fill better their needs. To prove the system functionalities, a tracking device simulator was written in Python, the result was satisfactory and all the requirements for the system has been met.